LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.